Manejo del dolor postoperatorio en urología. - Corral Rosillo, J.; Chicharro Almarza, J.; Delgado Martín, J.A.; Moreno Sierra, Jesús; Resel, Luis; Silmi Moyano, A. (Clínicas Urológicas de la Complutense, 1995)
Sin resumen